The relationship between parental neglect and cyberbullying perpetration among Chinese adolescent: The sequential role of cyberbullying victimization and internet gaming disorder - Gan, Xiong; Qin, Ke-Nan; Xiang, Guo-Xing; Jin, Xin (Frontiers in Public Health, 2023)
Cyberbullying perpetration and victimization have been common public health issues that have impaired the development of adolescent physical and mental health. Abundant research has proven associations between negative parental factors and cyberbullying perpetration. However, there is a paucity of research exploring the impact of parental neglect on cyberbullying and its internal mechanisms. Based on the parental acceptance-rejection theory (PARTheory) and the general aggression model (GAM), the present study constructs a sequential mediation model in which parental neglect is related to adolescent cyberbullying perpetration through cyberbullying victimization and internet gaming disorder (IGD). Using random cluster sampling, a total of 699 middle school students (Mage = 14.18 years, SD = 1.22, and 324 boys) were recruited from five schools in three provinces on mainland China. The participants completed questionnaires regarding parental neglect, cyberbullying perpetration, cyberbullying victimization, and IGD. The results of structural equation modeling indicated that parental neglect was positively associated with cyberbullying perpetration. The mediating effects of cyberbullying victimization and IGD in this relationship are significant both individually and jointly. The current findings have important implications for enlightening families and schools to pay particular attention to adolescents' experiences of parental neglect and provide them with timely feedback and assistance. This will contribute to the prevention and reduction of adolescent involvement in cyberbullying perpetration.